2006
DOI: 10.5771/0949-6181-2006-2-91
|View full text |Cite
|
Sign up to set email alerts
|

Inward FDI skilled labour, and product differentiation in the CEEC

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
0
7
1
Order By: Relevance
“…Thus, contrarily to the studies that concluded that there was a positive FDI impact, not only on the demand (Rutkowski 2006), but also on an increase in the offer of qualified labour (Slaughter 2002, Narula and Marin 2003, Cheung and Lin 2004, our study did not find any evidence supporting the idea that multinational firms have a higher level of human capital (formal education). Indeed, this relationship proved to be negative (Model 1), thus suggesting that FDI on its own does not seem to contribute to an increase in the level of human capital in the country.…”
Section: Downloaded By [Umeå Universitycontrasting
confidence: 79%
See 3 more Smart Citations
“…Thus, contrarily to the studies that concluded that there was a positive FDI impact, not only on the demand (Rutkowski 2006), but also on an increase in the offer of qualified labour (Slaughter 2002, Narula and Marin 2003, Cheung and Lin 2004, our study did not find any evidence supporting the idea that multinational firms have a higher level of human capital (formal education). Indeed, this relationship proved to be negative (Model 1), thus suggesting that FDI on its own does not seem to contribute to an increase in the level of human capital in the country.…”
Section: Downloaded By [Umeå Universitycontrasting
confidence: 79%
“…11 In our study, the level of R&D is measured in terms of the ratio of the firm's R&D expenses in the total sales (cf. Long and Ravenscraft 1993, Belderbos et al 2004, Rutkowski 2006. The size of the firm is measured in terms of number of workers (cf.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following are also considered as control variables: the firm's size, measured in terms of number of workers (Bob, René, Bert, and Roy 1997); the firm's age, calculated by the number of years the surveyed firms have been in activity (Rutkowski 2006); and the level of exports, measured from the ratio between each firm's exports on the sales value (Estrin, Meyer, Wright, and Foliano 2008). 4 The empirical results obtained from the estimation are shown on Table 1.…”
Section: Resultsmentioning
confidence: 99%